Extraction of Cu(ii) from aqueous phase using cooking palm oil as an organic solvent / Siti Fatimah Abdul Halim, Chang Siu Hua and Ana Najwa Mustapa - Abdul Halim, Siti Fatimah; Chang, Siu Hua; Mustapa, Ana Najwa (Research Management Institute (RMI), 2012)
Heavy metal is a source of contaminants in the industries effluents. It can be released into the environment in gaseous, particulate and transportation, microelectronic product and finally waste disposal (Bradl, 2005). For instance, generation of heavy metal waste has been estimated to be 4000 and 150,000 tonne/year alone in Portugal and European countries (Silva et al., 2005). This show that amount of waste being generated annually is respectively a huge amount. Therefore, heavy metal needed to remove from the sources to avoid contaminations to the environment and human health. Solvent extraction is one of the effective techniques to remove Cu(ll) from aqueous solution. The common conventional solvents used are petroleum- base such as such as kerosene, chloroform, dichloromethane, ndodecane, isododecane, ndecanol, n-heptane, n-hexane and cumene. These petroleum-based diluents, which form the bulk components in the organic phase, are usually toxic, non-renewable, non biodegradable, flammable and volatile in nature (Venkareswaran et al., 2007). They are difficult to handle and will result in ecological hazard to the aquatic systems in the case of solvent loss due to entrainment in the aqueous phase. Hence, it is essential to find a greener replacement for the conventional petroleum-based organic solvents in order to curb the environmental problem. Cooking palm oil which has a great potential as greener substitutes for the conventional solvents owing to their outstanding characteristics such as nontoxicity, inflammability, nonvolatility, renewability and biodegradability. The unlimited bioresources, as well as relatively simpler processing steps and technologies involved, ensure the use of cooking palm oils as solvent substitutes cheaper than the conventional organic solvents.